2012
DOI: 10.1186/1758-5996-4-39
|View full text |Cite
|
Sign up to set email alerts
|

Difference between the prevalence of symptoms of depression and anxiety in non-diabetic smokers and in patients with type 2 diabetes with and without nicotine dependence

Abstract: BackgroundIndividuals with diabetes who are smokers have higher risks of cardiovascular disease, premature death, and microvascular complications. The present study aims to determine the prevalence of symptoms of depression and anxiety in smokers with type 2 diabetes mellitus (T2D) and to evaluate if the prevalence of symptoms of depression and anxiety differ between the three groups studied (patients with T2D who smoke; patients with T2D who do not smoke; smokers without T2D), and finally determine if the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
2
3
0
2
Order By: Relevance
“…In the current study, patients with moderate to high nicotine dependence showed younger age <70. It is consistent with results in previous studies: two studies included COPD patients and the other included diabetic patients 12 13 17 . However, another two studies 18 21 showed higher nicotine dependence in older smokers: one study was population-based and the other study enrolled subjects with depressive or anxiety disorders.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, patients with moderate to high nicotine dependence showed younger age <70. It is consistent with results in previous studies: two studies included COPD patients and the other included diabetic patients 12 13 17 . However, another two studies 18 21 showed higher nicotine dependence in older smokers: one study was population-based and the other study enrolled subjects with depressive or anxiety disorders.…”
Section: Discussionsupporting
confidence: 92%
“…We investigated factors associated with nicotine dependence in current smokers of Korean COPD cohort. High education status was the most significant factor related to nicotine dependence in current smokers with COPD, which is consistent with a previous study 17 in current smokers with diabetes. They reported that nicotine dependence in smokers who had ≥8 years of formal education was 2.57 times higher than that in those with less education.…”
Section: Discussionsupporting
confidence: 92%
“…Con respecto a esto, los resultados mostraron que las personas con diabetes que consumían tabaco tuvieron puntuaciones estadísticamente significativas más altas en ansiedad y depresión como rasgo y estado, comparadas con quienes no fumaban. Estos resultados coinciden con la literatura, donde se ha mostrado que algunas personas fumadoras con DM presentan mayor sintomatología de ansiedad y depresión con respecto a quienes tienen DM y no fuman (Osme et al, 2012). Es importante resaltar que se observaron niveles medios tanto en depresión como ansiedad, exceptuando a la depresión como rasgo, que tuvo un nivel alto para todos los participantes, y la ansiedad como estado que fue alta sólo para los fumadores.…”
Section: Discussionunclassified
“…Con respecto a esto, diferentes estudios (Fabián & Cobo, 2007;Roy & Lloyd, 2012;Tovilla-Zárate et al, 2012) muestran que hay una asociación importante entre la ansiedad, depresión y la DM, y que tener el diagnóstico de DM representa mayor riesgo de tener síntomas de depresión, lo cual dificulta la adherencia al tratamiento y los cuidados de la enfermedad, lo que incrementa la probabilidad de consumir tabaco para modular la sintomatología de ansiedad y de depresión, y adicionalmente, dichos factores dificultan el cese de consumo de tabaco. Además, un estudio realizado por Osme et al (2012), mostró que en personas fumadoras con DM2, la prevalencia de síntomas de depresión y ansiedad son del 30 % y 50 % respectivamente, y la prevalencia de síntomas de ansiedad es mayor en comparación con quienes no fuman, con 19 % y 4.3 % respectivamente.…”
unclassified
“…The presence of symptoms of anxiety or depression is similar between patients who are dependent and not dependent on nicotine 18 . But Breslau et al demonstrated in young adults positive associations between nicotine dependence and major depression, obsessive compulsive type disorders, phobias, and anxiety disorders, as well as alcohol and illicit drug use.…”
Section: Sl No Situation Chance Of Dozingmentioning
confidence: 92%